Assessment in educational therapy - Marshall, Marion (Routledge, 2020)
Assessment in Educational Therapy offers essential grounding, skills, and ethical approaches for understanding and conducting assessments in the context of educational therapy. Six clear, straightforward chapters guide graduate students and trainees of the field to use scores, observation, and hypothesis testing to create strengths-based assessments and intervention strategies that can be delivered orally or in written reports. The book is the first to describe and critique all the standardized assessment instruments that qualified educational therapists can use to measure skills in reading, written expression, mathematics, and processing. Real-world case studies, practical takeaways of key concepts, resources for self-study, reflective questions, and other readers' tools enliven this comprehensive yet accessible reference
Description based on online resource; title from digital title page (viewed on March 09, 2020)
Keywords: Educational counseling; Students / Mental health